Fabrication and characterization of micro-dimple array on Al2O3 surfaces by using a micro-tooling - Roy, T.; Choudhury, D.; Azuddin, Mamat; Pingguan-Murphy, Belinda (Elsevier, 2014)
Al2O3 is a material with high potential for use in biomedical implants because of its low wear rate and excellent biocompatibility. The micro-dimpling surface technique is one of the most advanced surface modification techniques available for the optimisation of tribological performance. A well-defined dimple surface fabricated on an Al2O3 substrate could further improve its tribological properties, thus extending the durability of an implant. In this study, we fabricated a well-defined micro-dimple pattern on an Al2O3 surface by using a CNC micro machine, and characterised the fabricated dimple parameters. Mechanical analyses were conducted to investigate whether there are any changes in mechanical properties, and XRD testing was performed to detect the presence of foreign wear particles due to the fabrication procedures. Finally a friction testing was conducted replicating ceramic-on-ceramic hip joints. The outcomes of the study indicate the successful fabrication of three micro-dimple patterns averaging in diameter of 403.59 µm (SD 6.6325 µm) and averaging in depth of 20.97 µm (SD 2.1368 µm). There was a change in hardness, toughness and residual strength found in subsequent mechanical testing; nevertheless, no foreign wear debris was detected. Therefore, we conclude that the precision fabrication of a micro-dimple array of Al2O3 surfaces by using micro-tooling can be successfully executed without any significant degradation of mechanical properties. The tribology test showed a significant reduction in friction coefficient with these micro-dimple arrays.